2019
DOI: 10.4028/www.scientific.net/nhc.26.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dispersion Stability of Nanocarbons Using Zeta Potential in Distilled Water

Abstract: Nanocarbons (NCs) have exceptional mechanical, electrical, and thermal properties as compared to conventional carbon fibers. In previous studies, chemical agent has been used to disperse NCs in the colloid. The main objective of this study is to investigate the dispersion stability of NCs in distilled water and measurement the Zeta Potential value after using ultrasonic dispersion method (physics method). Two types of NCs were used in this study, carbon nanotube (CNT), and Carbon nanofiber (CNF) with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The effectiveness of fiber dispersion is directly correlated with the absolute value of the fiber surface potential, wherein a higher value indicates a superior degree of dispersion. Consequently, the zeta potential serves as a quantifiable and accurate measure of fiber dispersion in water, while also reflecting the stability of the fiber suspension (Alsharef et al, 2019). Ma et al (2011) employed zeta potential to compare the dispersion of CNTs in different solvents.…”
Section: Zeta Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of fiber dispersion is directly correlated with the absolute value of the fiber surface potential, wherein a higher value indicates a superior degree of dispersion. Consequently, the zeta potential serves as a quantifiable and accurate measure of fiber dispersion in water, while also reflecting the stability of the fiber suspension (Alsharef et al, 2019). Ma et al (2011) employed zeta potential to compare the dispersion of CNTs in different solvents.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…The optimal concentration ratio of MC to CNF was determined to be 2:1. Similarly, Alsharef et al (2019) evaluated the dispersion stability of CNTs and CNF in water using zeta potential and found that ultrasonic treatment enhanced the dispersion stability of carbon nanomaterials in water, with zeta potential values maintained above 50 mV. Thus, zeta potential serves as a valuable tool for quantitatively and accurately assessing the stability of fiber suspensions, including systems without dispersants.…”
Section: Zeta Potentialmentioning
confidence: 99%